STRATEGI PENGEMBANGAN USAHA PENANGKAPAN TUNA SKALA KECIL DI KABUPATEN SERAM BAGIAN BARAT; Penentuan Strategi Kemitraan dan Pola Bagi Hasil Optimal - Ramla Dula Saleh; Ruslan Tawari (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
This research was conducted to formulate strategy of developing business small scale tuna fishing in West Regency Seram. More specifically this study aims to determine the partnership strategy between fishermen and owners of capital and optimal profit sharing patterns for both parties. The analysis method used is descriptive analysis, profit analysis, BEP and UMP optimization, and simulation for optimal results. The results show that the ideal partnership strategy is to put forward the proportionality, fairness, fortune and sustainability aspects with the optimal profit sharing formulation is 48: 52, for fishermen and capital owners respectively.